Antioxidant and Skin Anti-Aging Effects of Marigold Methanol Extract - Kang, Chul Ho (Toxicol Res, 2018)
The objective of this study was to evaluate the antioxidant and anti-aging effects of marigold methanol extract (MGME) in human dermal fibroblasts. Total polyphenolic and flavonoid contents in MGME were 74.8 mg TAE (tannic acid equivalent)/g and 85.6 mg RE (rutin equivalent)/g, respectively. MGME (500 μg/mL) increased 1,1-diphenyl-2-picryl hydrazyl (DPPH) and 2,2′-azino-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical-scavenging, and superoxide dismutase (SOD)-like antioxidant activities by 36.5, 54.7, and 14.8%, respectively, compared with the control. At 1,000 μg/mL, these activities increased by 63.7, 70.6, and 20.6%, respectively. MGME (100 μg/mL) significantly increased the synthesis of type 1 procollagen by 83.7% compared with control treatment. It also significantly decreased Matrix Metalloproteinase-2 (MMP-2) activity and MMP-1 mRNA expression by 36.5% and 69.5%, respectively; however, it significantly increased laminin-5 mRNA expression by 181.2%. These findings suggest that MGME could protect human skin against photo-aging by attenuating oxidative damage, suppressing MMP expression and/or activity as well as by stimulating collagen synthesis.